Water Level and NPK Test of Bokashi Compost Fertilizer Results of Industrial Waste Processing Practical Work at the Mineral and Environmental Testing Laboratory - Fitri Junianti; Katrina Yanti Tumanan; Andi Ariatmasanti Aksan; Zaidatul Mabruroh; Iksan Adiasa (Fakultas Teknologi Industri - Universitas Muslim Indonesia, 2024)
Compost is one of the products resulting from the Industrial Waste Processing practicum in the form of solid waste. This compost goes through a composting process and becomes one of the organic fertilizers containing macro and micronutrients. Compost is produced through the biological decomposition process of organic material, which is controlled and results in humus. Moisture content is one of the key factors in the composting process, and it is essential for determining the maturity and quality of compost. Moisture content refers to the amount of water in a material or object, such as soil (also known as soil moisture), agricultural materials and products, rocks, etc. Additionally, compost fertilizer contains nutrients such as nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), and other elements. Based on testing, the sample rice husk: TSP 3:2:2 moisture content was 40.74%, and for another rice hull: TSP 3:2:2 sample, it was 43.14%. rice hull: TSP 3:2:2 had 0.74% for nitrogen content testing, and the second sample had 0.76%. Phosphorus content testing for rice husk: TSP 3:2:2 was 0.28%, while the second sample had 0.18%. rice husk: TSP 3:2:2 had 0.53% for potassium content testing, and the second sample had 0.509%. From these test results, it can be concluded that both samples meet the standards of SNI 19-7030-2004 for compost specifications from domestic organic waste. This research is expected to provide information on the quality of the bokashi fertilizer and be a reference in developing more optimal waste processing methods.